Foreshock and aftershock earthquakes characteristic for subduction (Case study: Aceh earthquake in 2004 and Tohoku earthquake, Japan 2011) - Rusnardi Rahmat Putra; Asri Atmojo (invotek, 2021)
Aceh earthquake occurred in 2004 with magnitude 8.8Mw, the epicenter was located at latitude 3.295 and longitude 95.982 and Tohoku earthquake occurred in 2011 with magnitude 9.0Mw and located at latitude 38.29 and longitude 142.373. The both earthquakes have similar earthquake source mechanism such as the epicenter located in subduction zone, plate movement type. The research aims to determine the distribution of earthquake events before (foreshock) and after (aftershock) the main shock. Earthquake event datas were obtained from several earthquake databases, such as USGS and BMKG. The earthquake events from database sources are grouped based on the time of occurrence, radius, and magnitude. The result for foreshock shows that the number of earthquake events for foreshock within two years at a radius of 150 km with a magnitude M> 4 as many as 12 earthquake events and 129 earthquake events for Aceh and Tohoku respectively, The result for aftershocks are 119 and 1576 for Aceh and Tohoku respectively.